2001
DOI: 10.1542/peds.107.3.e37
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Remission of Asthma in Schoolchildren: Report From the Obstructive Lung Disease in Northern Sweden Studies

Abstract: ABSTRACT.Objective. An increasing prevalence of asthma has been reported worldwide as well as in Sweden. In 1996, the prevalence of asthma and type 1 allergy was investigated in a cohort of 3525 children 7 and 8 years old in 3 areas of northern Sweden. The aim of the present study was to estimate the incidence of asthma and to identify risk factors for incident cases over 1 year.Methods. The study started with a parental questionnaire, the International Study of Asthma and Allergies in Childhood questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0
4

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 35 publications
6
42
0
4
Order By: Relevance
“…However, in the present analysis quitting smoking was found to favour remission of asthma. This finding is supported by RÖ NMARK et al [7], who concluded that remission of asthma is associated with cessation of smoking.…”
Section: Asthma Remission In Northern Europe M Holm Et Alsupporting
confidence: 56%
See 2 more Smart Citations
“…However, in the present analysis quitting smoking was found to favour remission of asthma. This finding is supported by RÖ NMARK et al [7], who concluded that remission of asthma is associated with cessation of smoking.…”
Section: Asthma Remission In Northern Europe M Holm Et Alsupporting
confidence: 56%
“…One of the few studies on asthma remission rate in adults investigated a cohort of 300 middle-aged and elderly subjects [7]. This study reported remission (no use of asthma medicines, no recurrent wheezing and no attacks of shortness of breath) in 6% of subjects at a follow-up 10 yrs after a validated diagnosis of current asthma, equivalent to a remission rate of six per 1,000 person-yrs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…large-scale studies on the epidemiology of COPD, asthma and type-1 allergy in Northern Sweden which started in 1985. (13,14) Today, longitudinal studies of a number of cohorts are under way, including a total of approximately 40,000 children, adults, and elderly persons. The first survey of the second cohort of the OLIN studies included pulmonary function tests performed from 1993 to 1995 on 1,900 subjects born in 1925-26, 1940-41, 1955-56 and 1970-71.…”
Section: Study Samplementioning
confidence: 99%
“…5,16 The Obstructive Lung Disease in Northern Sweden studies have reported on the prevalence and incidence of asthma, allergic diseases and sensitization in children, as well as associated factors such as damp housing, environmental tobacco smoke, and traffic-related air pollution since 1996. 12,[17][18][19][20][21] In the current study, a well-defined cohort of asthmatic children derived from the first pediatric Obstructive Lung Disease in Northern Sweden Studies cohort was followed annually from age 7-to 8-years to age 19 years. The aim was to study the remission and persistence of asthma, as well as to determine any correlated factors.…”
mentioning
confidence: 99%